School-Age Outcomes of Very Preterm Infants After Antenatal Treatment With Magnesium Sulfate Versus Placebo. Issue 3 (September 2015) - Doyle, L.W.; Anderson, P.J.; Haslam, R.; Lee, K.J.; Crowther, C.
<x xml:space="preserve">Abstract</x> (JAMA. 2014 ;312(11):1105–1113)